Surgery for Left Ventricular Outflow Tract Obstruction with a Relatively Thin Interventricular Septum - Shingu, Yasushige; Sugiki, Hiroshi; Ooka, Tomonori; Kato, Hiroki; Wakasa, Satoru; Tachibana, Tsuyoshi; Matsui, Yoshiro (The Thoracic and Cardiovascular Surgeon, 2018)
Background To examine the results of myectomy and mitral valve surgery for systolic anterior motion (SAM) of the mitral valve and left ventricular outflow tract obstruction (LVOTO) with a relatively thin interventricular septum.Methods The subjects were 12 patients with SAM and LVOTO. Eight had hypertrophic obstructive cardiomyopathy (HOCM) with a mean interventricular septal thickness of 16 mm. Three had sigmoid septum and one had an unknown etiology. For HOCM, isolated extended myectomy was performed when mitral regurgitation was mild (n = 1) and extended myectomy plus mitral valve surgery was performed when mitral regurgitation was more than mild (n = 4) or primary valve etiologies existed (n = 3). Myectomy was performed for the three cases with sigmoid septum. Myectomy plus height reduction of the posterior mitral leaflet was performed for the one case with the unknown etiology of SAM.Results In the patients with HOCM, the maximum LVOT pressure gradient significantly decreased from 140 ± 18 to 16 ± 6 and 3 ± 3 mm Hg, while mitral regurgitation significantly decreased from 2.3 ± 0.5 to 0.5 ± 0.3 and 0.4 ± 0.2 at pre-op, early post-op, and last follow-up (3 ± 1 years), respectively. In the other etiologies, the maximum LVOT pressure gradient changed from 56 ± 15 to 25 ± 15 and 5 ± 4 mm Hg; mitral regurgitation changed from 2.0 ± 0.6 to 1.3 ± 0.3 and 1.3 ± 0.8, at pre-op, early post-op, and the last follow-up (3 ± 2 years), respectively.Conclusion Myectomy with mitral valve surgery is an option for SAM and LVOTO in patients with a relatively thin interventricular septum.
Keywords: cardiomyopathy; mitral valve surgery; systolic anterior motion